STRENGTHENING LEGAL AND HEALTH UNDERSTANDING IN PREPARATION FOR MARRIAGE THROUGH PREMARITAL SEMINAR IN TAPOS I VILLAGE, TENJOLAYA DISTRICT, BOGOR REGENCY - Hasan, Muhammad Syahrul; Khoirunnisa, Amaliyah; Jalil, Muhammad (STAI Al-Hidayah Bogor, 2024)
Marriage is an important step in life that requires thorough preparation from various aspects. The lack of understanding regarding prenuptial law and health in Tapos I Village, Tenjolaya District, Bogor Regency, can lead to issues in household life. This community service aims to enhance the understanding of engaged couples about legal and health aspects in marriage preparation. The method used is a prenuptial seminar involving the local Office of Religious Affairs (KUA) as marriage specialists and healthcare professionals as resource persons. The material presented covers legal aspects (marriage registration process, required documents, the rights and obligations of the couple, and legal protection) and health aspects (physical health, mental health, education on infectious diseases, and healthy lifestyles). The results show an increase in the participants' knowledge and awareness of these two aspects, as demonstrated by their enthusiasm and active participation during the question-and-answer session. Participants also reported higher confidence in facing marriage. In conclusion, the prenuptial seminar proved effective in strengthening the understanding of engaged couples, and it is expected to help create harmonious and prosperous families in Tapos I Village. Recommendations for the sustainability of this program include regular implementation and expansion to nearby villages.